Penggenapan Janji Allah berdasarkan Nehemia 6:15 dalam Mendidik Anak - Yulianus Bani; Purwisasi Yuli (Sekolah Tinggi Agama Kristen Samarinda, 2022)
Abstract: The teaching of God's promises comes from the Bible. God's promise is something that cannot be separated from the identity of God. God's promise is very important for the Israelites as evidence of the revelation of faith from Abraham, Isaac and Jacob who is known as the living God. God's promise is a manifestation of absolute truth because once God promises then He will fulfill His promise. If God's promise is not fulfilled, it can be said that God's promise is relatively changing according to the situation and this is one proof that it is not God. Children must believe in God's promises in life as a provision for their faith in the future. The future generations of this nation must have coverage under any circumstances God is still with His children. Parents have a role in explaining and providing children with evidence from the Bible for God's fulfillment for the Israelites and believers today. God this is so important because it was commanded by Moses to be delivered to the Israelites. The Israelites were to teach all the statutes and promises of God to their children from generation to generation day and night. All of this is intended so that they know their identity as children of God. The results of this study provide evidence that God's promise is the realization of absolute truth. God's promises are absolute truths that every human of His choice must believe.Abstrak: Pengajaran tentang janji Allah murni bersumber dari Alkitab. Janji Allah merupakan hal yang tidak dapat dipisahkan dari jati Diri Allah. Janji Allah sangat penting bagi umat Israel sebagai bukti penyataan iman dari Abraham, Ishak dan Yakub yang dikenal sebagai Allah yang hidup. Janji Allah merupakan wujud kebenaran absolut karena sekali Allah berjanji maka Ia akan menggenapi janjiNya. Jika janji Allah tidak digenapi maka dapat dikatakan bahwa janji Allah itu sifatnya relative karena berubah sesuai situasi dan ini salah satu bukti bukan Allah. Anak-anak harus menyakini janji-janji Allah dalam hidup sebagai bekal imannya di masa depan. Generasi masa depan bangsa ini harus memiliki pengharapan bahwa dalam situasi apapun Allah tetap menyertai anak-anakNya. Orang tua memiliki peran untuk menjelaskan dan memberikan bukti-bukti dari Alkitab kepada anak-anak penggenapan Allah bagi umat Israel dan orang percaya masa kini. Allah melihat hal ini sangat penting karena itu diperintahkan kepada Musa untuk disampaikan kepada orang Israel. Orang Israel harus mengajarkan semua ketetapan dan janji-janji Allah kepada anak-anak mereka turun temurun siang dan malam. Semua ini bertujuan agar mereka mengetahui identitasnya sebagai anak-anak Allah. Hasil penelitian ini memberikan bukti bahwa janji Allah merupakan realisasi kebenaran absolut. Janji Allah adalah kebenaran absolut yang harus dipercayai oleh setiap manusia pilihanNya.